G20, IMF und WTO in turbulent times: Legitimacy and effectiveness put to the test - Katharina Gnath; Stormy Mildner; Claudia Schmucker (Stiftung Wissenschaft und Politik (SWP), 2012)
The global economic and financial crisis was an enormous challenge for national economic policy-making and a vivid illustration of how important it is to have a well-functioning system of global economic governance. The newly founded G20, representing the world's major economies, assumed a key role in managing the crisis. In the face of the fragile global financial system and the severe contraction in world trade, the International Monetary Fund (IMF) and the World Trade Organization (WTO) faced immense challenges as well. During the turbulent years immediately following the crisis, these three institutions were granted more leeway than usual to chart new courses. But the risk of failure was also particularly high. How well did the G20, IMF, and WTO handle the crisis? To answer this question systematically, we subject their effectiveness and perceived legitimacy during this period to critical evaluation. All three institutions show deficits in these areas. If they worked together more closely in the future instead of acting independently, they could improve the long-term effectiveness and legitimacy of the entire governance system. The G20 needs to take a more vigorous leadership role in setting the international agenda and in providing a political impetus. As a steering organization, it can help to reduce the inertia and fragmentation of the global governance system. The more institutionalized organizations IMF and WTO can, for their part, ensure that rules are formulated, adapted, and implemented more consistently
Keywords: 320